2021
DOI: 10.1158/1055-9965.epi-19-1537
|View full text |Cite
|
Sign up to set email alerts
|

Black and White Differences in Colorectal Cancer Screening and Screening Outcomes: A Narrative Review

Abstract: Racial disparities in colorectal cancer incidence are widely documented. There are two potential mechanisms for these disparities: differences in access to screening, including screening follow-up, and differences in underlying risk of colorectal cancer. We reviewed the literature for evidence of these two mechanisms. We show that higher colorectal cancer incidence in blacks relative to whites emerged only after the dissemination of screening and describe evidence of racial disparities in screening rates. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 77 publications
2
39
0
Order By: Relevance
“…4 In 2016, 25.6% of eligible adults in the US had never been screened for colorectal cancer 5 and in 2018, 31.2% were not up to date with screening. 6…”
Section: Importancementioning
confidence: 99%
“…4 In 2016, 25.6% of eligible adults in the US had never been screened for colorectal cancer 5 and in 2018, 31.2% were not up to date with screening. 6…”
Section: Importancementioning
confidence: 99%
“…While the CRC occurrence in men was predominantly higher than in women, 30 , 85 , 86 less is seen in the screening policy that stratifies sex as the eligible individuals. Only two guidelines proposed the risk score consisting of age, sex, family history, and smoking as an effort to prioritize screening among average-risk individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Lebwohl et al demonstrated significantly higher ADR and prevalence of adenoma and advanced adenoma in African Americans in comparison with Caucasians [ 13 ]. However, a recent review indicates mixed evidence in ADR and prevalence of adenomas among African Americans and Caucasians [ 22 ].…”
Section: Discussionmentioning
confidence: 99%